Substansi Perayaan Maulid Nabi Muhammad S.A.W. (Tinjauan Historis dan Tradisi di Indonesia) - Edi Kurniawan Farid (HUMANISTIKA : Jurnal Keislaman, 2016)
Prophet's Birthday is celebrated widely throughout the world, including in Indonesia, many cultural traditions influence of this warning. There are two opinions that suggest the early emergence of Mawlid tradition, first held by the Deputy Mu'iz li Dinillah, and during the Sultan Salahuddin al-Ayubi. Prophet's Birthday celebrations are a tradition in the Islamic community some time after the Prophet Muhammad died. The warning for Muslims is a tribute and a reminder of the greatness and the example of Prophet Muhammad with various forms of cultural activities, rituals and religion.